Nobody's fool - Katz, James C.; Denny, Jon S.; Purcell, Evelyn (Metro Goldwyn Mayer, 1986)
Small-town girl Cassie has made a few big mistakes in love...including an attempted stabbing! Labeled a kook by some, and largely avoided by all. Cassie wallows in shame and self-pity...until a traveling Shakespearean troupe arrives and she falls for a hot backstage roadie. Can she trust this stranger offering romance and a one-way ticket out of town? Or will she find that, in the words of the Bard, "the course of true love never did run smooth"?.